2022
DOI: 10.1111/jpm.12875
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence screening in a public mental health service: A qualitative examination of mental health clinician responses to DFV

Abstract: What is known on the subject?• Mental health clients experience higher estimated rates of domestic violence, yet mental health services are less likely to screen for domestic violence. What the paper adds to existing knowledge?• This paper qualitatively explores the perspectives and experiences of mental health practitioners in inpatient and community teams in a publicly funded hospital and health service (i.e. public mental health service).• Mental health practitioners described a lack of domestic violence tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A recent qualitative study of health professionals working in an Australian mental health service reported a perceived lack of domestic and family violence training, and a perceived lack of knowledge about domestic violence and the available services to support people when domestic violence is disclosed (Gillespie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent qualitative study of health professionals working in an Australian mental health service reported a perceived lack of domestic and family violence training, and a perceived lack of knowledge about domestic violence and the available services to support people when domestic violence is disclosed (Gillespie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Participants reported that screening for domestic and family violence was not something that they 'automatically' considered as part of their care (Gillespie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature highlighted the lack of training provided for healthcare providers to screen DV cases, thereby weakening their ability to probe DV questions and the lack of empathic listening skills during consultations. As such, DV survivors easily suffer from delayed treatment or referral from physicians [57]. For future endeavors, DV training development can extend the targeted participants to more healthcare professionals who might be poorly equipped, such as new nursing staff, social workers, or counselors during the orientation program.…”
Section: Hit Interventions Thrives In Urban and Rural Areasmentioning
confidence: 99%